1993
DOI: 10.1073/pnas.90.21.10056
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and functional expression of a cDNA encoding glycosylation-inhibiting factor.

Abstract: By using probes based on partial amino acid sequence of glycosylation-inhibiting factor (GIF) from a mouse T-cell hybridoma, a fufl-length cDNA encoding mouse GIF was isolated. A cDNA clone encoding human GIF was isolated from cDNA libraries of a GIF-producing human T-cell hybridoma by using mouse GIF cDNA as a probe. The cDNAs encode a putative 12.5-kDa peptide of 115 amino acids. Northern blot analysis demonstrated a single, 0.6-kb transcript. Polydonal rabbit antibodies against the Escherichia cofi-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 25 publications
0
50
1
Order By: Relevance
“…It is noteworthy that no inhibition of MIF enzymatic activity was obtained with the thiol-reactive agents iodoacetamide (17) and N-ethylmaleimide (18), suggesting that NAPQI and HQ are reacting at sites other than free cysteines present in MIF. The efficiency of MIF enzyme inhibition by the quinones varied according to the concentration of MIF present in the reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that no inhibition of MIF enzymatic activity was obtained with the thiol-reactive agents iodoacetamide (17) and N-ethylmaleimide (18), suggesting that NAPQI and HQ are reacting at sites other than free cysteines present in MIF. The efficiency of MIF enzyme inhibition by the quinones varied according to the concentration of MIF present in the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…MIF has the capacity to override, or counterregulate, the immunosuppressive effects of glucocorticoids (5,6,8,10), which accounts in part for the proinflammatory role of MIF in conditions such as septic shock (5,6,(11)(12)(13), arthritis (14)(15)(16), and glomerulonephritis (17). Additional biological activities for MIF include the regulation of macrophage and T cell activation (7,8), IgE synthesis (18), insulin release (19) and carbohydrate metabolism (20,21), cell growth and apoptosis (22,23), and tumor angiogenesis (24).…”
mentioning
confidence: 99%
“…The genomic sequence of hMIF was recently elucidated by Paralkar and Wistow (1994) and the sequence is identical to that encoded by the cDNA of hGIF which was derived from T-cells by Mikayama et al (1993). It remains to be established if the cDNA sequence of hMIF given by Weiser et al (1989) is an isoform of hGIF or is due to a sequencing error.…”
Section: Discussionmentioning
confidence: 99%
“…The cDNAs encoding MIF-like proteins were also isolated from a chicken embryonic eye lens library (Wistow et al, 1993) and a mouse cDNA library in the class of delayed early response genes (Lanahan et al, 1992). The latter appears to have identical amino acid sequence to murine glycosylation-inhibiting factor (GIF) which has the ability to switch normal T-cells from production of glycosylated IgE-binding-factor complex to formation of the unglycosylated complex (Mikayama et al, 1993;Gomi et al, 1994). We have recently isolated two isoforms of a 12-kDa protein (pl2" and ~1 2~) from calf brain tissues and showed that their N-termini share a high sequence similarity with that of human (h)MIF .…”
mentioning
confidence: 99%
“…GIF is encoded by the same gene that codes for macrophage migration inhibitory factor (MIF) (5). It is highly conserved throughout the animal kingdom although it does not belong to any cytokine gene family.…”
mentioning
confidence: 99%